Chutes or Ladders? A Longitudinal Analysis of Immigrant Earnings - Lubotsky, Darren (Journal of Political Economy, 2007)
I use longitudinal earnings data from Social Security records to study the effect of selective emigration on the measured progress of im-migrants to the United States. The immigrant-native earnings gap closes by 10–15 percent during immigrants ’ first 20 years in the United States, or about half as fast as typical estimates from repeated cross sections of the decennial census. The divergent results indicate that emigration by low-wage immigrants has systematically led past re-searchers to overestimate the wage progress of immigrants who remain in the United States. Selective back-and-forth migration also leads typical estimates to overstate the measured decline in earnings among successive immigrant arrival cohorts between 1960 and 1980. I.